Preventive Action of Blue Lotus (Nymphaea Caerulea) Flower Extract against E. Coli-Induced Immune-Pathological Changes In Gallus gallus domesticus Embryo.: Preventive Action of Blue Lotus Flower Extract against E. Coli-Induced Immune-Pathological Changes In Gallus gallus domesticus Embryo - Satadal Das; Subhanjana Mukherjee; Debasmita Chatterjee; Banhishikha Singh; Krishnendu Paira (International Journal of Applied Biology, 2023)
Nymphaea caerulea is an aquatic plant originally found in the Nile River has several therapeutic activities - anti-depressant, anti-inflammatory, anti-oxidant, and anti-microbial activities. This led us to perform the study focusing on the anti-microbial properties of the flower extract. Crude ethanolic extract of petals and pollens of N. caerulea flower were prepared and its antimicrobial activity was checked against E. coli. The Minimum Inhibition Concentration value was determined showing that both the extracts had similar capability against both the strains, with MIC value of 0.39mg/ml and 0.78mg/ml MIC against E.coli ATCC and MDR strains respectively. Further studies were done to study the gross morphological changes and the genetic expression changes of IL-10 and IFN-γ in E. coli-infected Gallus gallus domesticus embryo models. From the results, it can be said that the extract has preventive effects that reduce haemorrhages of the embryos when infected with E. coli. Moreover, there was slight increase in the level of IL-10 cytokine gene expression indicating its anti-inflammatory action along with a higher increase in the IFN-γ cytokine gene expressions responsible for activating the host immunity. Thus, the findings indicate the probable potential role of N. caerulea flower extract to act as an antibacterial agent.